Ribosomal highly basic 23-kDa protein as a reliable standard for gene expression analysis - Jesenofsky, Ralf; Backhaus, C.; Ringel, Jörg; Löhr, J.-Matthias (Pancreatology, 2002)
Background/Aims: Analysis of gene expression is dependent on normalization using housekeeping genes. However, many of these housekeeping genes (e.g. GAPDH, ß-actin) are upregulated in chronic pancreatitis and pancreatic cancer, and cannot be used for normalization. For this reason we tried to identify a housekeeping gene useful for expression analysis in pancreatic diseases. Methods: RNA isolated from various tissues and states of disease was subjected to reverse transcription and subsequently amplified by PCR using primers for GAPDH and for the ribosomal highly basic 23-kDa (rb 23kDa, RPL13A) protein. Results: As anticipated, expression of GAPDH varied markedly in the different tissues, whereas the expression of rb 23-kDa was constant in all samples investigated. Conclusion: We recommend the use of the ribosomal highly basic 23-kDa protein as a standard for normalization at least for the pancreas and the prostate.
Elektronische Reproduktion der Druckausgabe
Gesehen am 24.05.2022